2015
DOI: 10.1007/s00213-014-3860-3
|View full text |Cite
|
Sign up to set email alerts
|

Age-dependent changes in cocaine sensitivity across early ontogeny in male and female rats: possible role of dorsal striatal D2High receptors

Abstract: Rationale Responsiveness to acute psychostimulant administration varies across ontogeny. Objective The purpose of the present study was to determine if age-dependent changes in D2High receptors may be responsible for the ontogeny of cocaine sensitivity in preweanling, adolescent, and adult rats. Methods [3H]-Domperidone/dopamine competition assays were used to determine ontogenetic changes in the proportion of D2High receptors in male and female preweanling [postnatal day (PD) 5, 10, 15, and 20], adolescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 64 publications
4
15
1
Order By: Relevance
“…Ontogenetic changes in D2 receptors may be partially responsible for differences in psychostimulant sensitivity (McDougall et al 2015) since functionality of the D2 receptor continues to mature beyond the preweanling period (Der-Ghazarian et al 2014) and likely through adolescence. Other groups, assessing D2 density via autoradiography after early MPH exposure (PND 21) do not report enduring effects of the drug on either D1 or D2 density (Gill et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Ontogenetic changes in D2 receptors may be partially responsible for differences in psychostimulant sensitivity (McDougall et al 2015) since functionality of the D2 receptor continues to mature beyond the preweanling period (Der-Ghazarian et al 2014) and likely through adolescence. Other groups, assessing D2 density via autoradiography after early MPH exposure (PND 21) do not report enduring effects of the drug on either D1 or D2 density (Gill et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Because of the potential translational relevance to young humans (Spear 2000; Andersen 2003), we compared rats from the preadolescent (PD 21–25) and adolescent (PD 41–45) periods (for a discussion of ontogenetic epochs, see Smith 2003; Frantz et al 2006). Based on previously cited adult ketamine studies, as well as ontogenetic data using psychostimulants (Becker et al 2001; Parylak et al 2008; McDougall et al 2015), it was hypothesized that adolescent female rats would show stronger unconditioned and conditioned locomotor activity than male rats. Preadolescent rats were also hypothesized to show robust ketamine-induced unconditioned and conditioned activity, but no sex differences were predicted in this prepubertal age group.…”
Section: Introductionmentioning
confidence: 99%
“…In adult rats, for example, females are often hyperresponsive to an acute injection of cocaine [71,72], and show a more pronounced sensitized response than do male rats [73,74]. Prepubescent rats, on the other hand, do not typically exhibit sex differences in locomotion or sensitized responding after DA agonist treatment [7580]. Consistent with these past studies, we found that cocaine did not differentially affect the locomotor activity of male and female preweanling rats on the pretreatment day, or cause sex-dependent differences in sensitized responding on the test day.…”
Section: Discussionmentioning
confidence: 99%